The voyage of the Komet along the Northern Sea Route, 1940 - Armstrong, Terence (Polar Record, 1949)
Early in 1940 the German naval high command, acting through the German naval attaché in Moscow, opened negotiations with the Soviet Navy for the passage of two ships along the Northern Sea Route in the summer of that year. Agreement with the Soviet naval authorities was reached, possibly without the knowledge of the Soviet Government. The operation was to be carried out in the strictest secrecy, and a sum of 850,000 roubles (calculated on the expenses of the icebreakers involved) was to be paid by the Germans. Preparations accordingly went forward. One of the two ships was obliged for some reason to drop out, leaving only the other, the raider Komet , to make the voyage. The Komet was a converted merchant ship of 3300 gross registered tons driven by Diesel motors. She had a top speed of 14 knots. Special preparations for running in ice included strengthening the hull and screw and testing the steering gear more severely than usual: the special type of screw with removable blades, as used by Russian ships for ice passages, was not available. Her commander was Kapitan, later Konteradmiral, Robert Eyssen. He had worked in the 1930'sfor Hydrografisches Amt des OKK (Hydrographic Office of the German naval high command), and while first officer and later commander of the survey vessel Meteor had had experience in ice navigation off East Greenland. The crew numbered 270, but included no meteorologists or hydrographers. From the commander's point of view, one of the most useful members of the crew was his interpreter, a man referred to in reports as Agent Kroepsch, a person of unknown allegiance. Krbepsch's knowledge of Russian enabled the commander to get a clearer picture of the changeable and, to him, most suspicious attitude of the Russians towards the voyage, and to act accordingly. The voyage itself was remarkable because it showed that with the assistance of icebreakers and good ice and weather conditions very fast time can be made—in fact the voyage was the fastest ever made up to that date.